ANALISIS KANDUNGAN KAFEIN DALAM KOPI SUMATERA DAN KOPI FLORES DENGAN VARIASI SIKLUS MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Nadhirah -; Alimuddin -; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
The research about analysis of caffeine content on coffee Sumatera and coffee Flores with cycle variations using spectrophotometer UV-Vis has been done. Coffee extract obtained through soxhletation with ethanol 96% and variation cycles used is 3, 6, 9, 12 and 15. The extract obtained is dissolved in ethanol 96% and tested with spectrophotometer UV-Vis at a wavelength of 272 nm. The result obtained in this research is the caffeine content in coffee Sumatera for 3, 6, 9, 12, 15 cycles consecutive are 0.582 mg/L; 0.986 mg/L; 1.315 mg/L; 2.143 mg/L and 2.918 mg/L. While the caffeine content obtained coffee Flores for 3, 6, 9, 12, 15 cycles consecutive are 0.465 mg/L; 0.599 mg/L; 0.728 mg/L; 1.186 mg/L and 1.653 mg/L.Keywords : Coffee Sumatera, Coffee Flores, Ethanol 96%, Soxhletation, Caffeine, Spectrophotometer UV-Vis